Performance of an inorganic optical fiber dosimeter for external beam radiation therapy. (August 2018) - Alharbi, Majed; Martyn, Michael; Chen, Lingxia; Gillespie, Sean; Woulfe, Peter; O'Keeffe, Sinead; Foley, Mark
Abstract : Modern radiation therapy treatment techniques and delivery methods introduce new challenges to existing dosimetry systems. As a result, much research has been conducted on the development of a radiation dosimetry system based on scintillating optical fibre. They offer many advantages over the currently employed dosimeters for real time dosimetry. Optical Fibre dosimeters (OFD) have small dimensions, are immune to electromagnetic fields and can be used to remotely monitor radiation in real time. For this study a novel OFD based on an inorganic scintillating material for external beam radiotherapy was developed. The dosimeter was constructed using a PMMA (polymethyl methacrylate) plastic optical fibre. The core of the PMMA was micro machined to make a 700 μm diameter and 7 mm deep cavity. The scintillating material, terbium doped gadolinium oxysulphide (Gd2O2S:Tb) was filled in the cavity and sealed with an epoxy. The scintillation material fluoresces on exposure to ionising radiation and the resultant emitted fluorescent light is detected using a multi-pixel photon counting module. Measurements to date using the novel dosimeter demonstrate very good repeatability and reproducibility with only a maximum of 0.17% and 0.68% difference from the average value, respectively. The results also show excellent linearity of the output signal with radiation doses and the dosimeter response was independent of dose rate. However, the percentage depth dose measurements showed an over response of the OFD compared to an ionization chamber. These differences are being investigated by means of Monte Carlo simulations.